Educational Approach to Increase Student Pharmacist Confidence with Medicare - Adriane Irwin (University of Minnesota Libraries Publishing, 2021)
Objective: To describe a didactic, case-based approach to teach student pharmacists about Medicare enabling them to consider the spectrum of coverage options, as well as both medical and drug needs, when assessing insurance plans. Innovation: Education on Medicare often focuses on Part D.   However, the growing popularity of Medicare Advantage plans requires students to have a more comprehensive understanding of Medicare.  To address this gap, a didactic, case-based approach was developed where students received four 90-minute lectures on Medicare and then applied the information through a patient case.   Data was collected on student-reported confidence with Medicare, and attitudes towards the importance of understanding insurance in improving patient care.  Surveys were conducted at baseline, after the didactic lectures (interim survey), and upon project completion (final survey).  Key Findings: Confidence with Medicare increased between the baseline and interim survey (all p ≤ 0.001).  Additional gains were seen after completing the project in helping patients navigate financial assistance programs (p ≤ 0.001) and selecting specific plans (p ≤ 0.05).  After the interim survey, students more strongly agreed with statements related to knowledge of insurance as an opportunity to help advocate for patients (p ≤ 0.001), and the need to consider Medicare coverage when making medication recommendations (p ≤ 0.05) Conclusion: The combination of didactic lectures and a case-based exercise positively impacted self-reported student confidence in their knowledge, as well as attitude towards Medicare.   Increasing student confidence in Medicare and willingness to engage beneficiaries in conversations about insurance coverage may be a strategy to improve patient care and health outcomes.